2022
DOI: 10.1016/j.spinee.2022.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for L5 pedicle fractures after single-level posterior spinal fusion

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…A previous study has demonstrated that patients with high PI, high LL, and high SS may be at risk of developing pedicle fractures. 15 Interestingly, however, the study demonstrated no significant difference in PI-LL mismatch between fracture and nonfracture groups, suggesting that spinopelvic imbalance may not successfully predict this fracture. We believe that the anterior shift of the loading axis in the lumbosacral region is associated with excessive shear force on the pedicle.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A previous study has demonstrated that patients with high PI, high LL, and high SS may be at risk of developing pedicle fractures. 15 Interestingly, however, the study demonstrated no significant difference in PI-LL mismatch between fracture and nonfracture groups, suggesting that spinopelvic imbalance may not successfully predict this fracture. We believe that the anterior shift of the loading axis in the lumbosacral region is associated with excessive shear force on the pedicle.…”
Section: Discussionmentioning
confidence: 73%
“…Recently, Wanivenhaus et al 15 reported a case-control study of L5 pedicle fracture after L4–5 PLIF/TLIF and stated that the frequency of this complication is 3.2%. However, their study is currently the only report from a single institute, and no similar cases have been reported in other articles investigating L5–S1 adjacent segment disease (ASD) after L4–5 fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar instrumentation is a very common surgical procedure in degenerative diseases of the lumbar spine and postoperative evaluation is routinely performed by standard radiographs as first-line imaging, usually with anteroposterior and lateral views [ 1 , 2 ]. In a subset of patients, especially with persistent pain, an additional CT scan is performed to exclude fractures, misplacement or loosening of metal implants [ 3 ]. However, this results in a much higher total radiation dose for the patient compared to the evaluation with radiographs, despite the benefit of detailed cross-sectional anatomic information provided by the CT [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%